COUPLED-OSCILLATORS IN THE SWIMMING LAMPREY MOVEMENT - SITI MERRIAM MANIHURUK, MONIK
Coupled-oscillators in swimming lamprey is one of oscillation phenomena occurs in nature. Oscillatory motion in lamprey is found on the ventral root segments of the spinal cord. Researchers conducted an experiment to observe the oscillatory movement by putting electroda on the ventral root segment of the lamprey spinal cord. The results indicate the existance of periodic bursts. In this final project, oscillation phenomena between spinal segments of lamprey will be reviewed as a coupled oscillators, using mathematical model of Kuramoto equation. A system with only two oscillators will be considered here. It will be shown that the harmonic motion is a stable, and the movement of neighbours segments have a constant phase difference. This result confirm the experimental observation.